Clinical implication of electrocardiogram change in patients experiencing lung transplantation with end stage lung disease - Leem, Ah Young; Yu, Hee Tae; Sung, MinDong; Chung, Kyung Soo; Kim, Yeonkyeong; Woo, Ala; Kim, Song Yee; Park, Moo Suk; Kim, Young Sam; Yang, Young Ho; Kim, Ha Eun; Lee, Jin Gu; et al. (Frontiers in Physiology, 2024)
Introduction: End-stage lung disease causes cardiac remodeling and induces electrocardiogram (ECG) changes.On the other way, whether lung transplantation (LTx) in end-stage lung disease patients are associated with ECG change is unknown. The object of this study was to investigate ECG changes before and after LTx in end-stage lung disease patients and whether these changes had clinical significance.This was a single-center retrospective cohort study of 280 end-stage lung disease patients who consecutively underwent LTx at a tertiary referral hospital. ECG findings before LTx and within 1 week and 1, 3, and 6 months after LTx were obtained and analyzed. To find clinical meaning, the ECG at 1 month after LTx was analyzed according to 1-year survival (survivor vs. non-survivor groups). Survival data were estimated using the Kaplan-Meier method.Results: Significant differences were observed in the PR interval, QRS duration, QT interval, QTc interval, and heart rate before LTx and 1 month after LTx; the PR interval, QRS duration, QTc interval, and heart rate were decreased. Particularly, the QTc interval was significantly decreased 1 month after LTx, whereas there was no significant change in the QTc interval from 1 to 6 months thereafter. The PR interval, QT interval, QTc interval, and heart rate were significantly different between the survivor and non-survivor groups. The serial changes in QTc interval before LTx and 1 and 3 months after LTx were also significantly different between the survivor and non-survivor groups (P=0.040 after adjusting for age and body mass index). Upon dividing the patients based on the range of QTc interval change ≤-8ms, >-8-10ms, >10-35ms, >35ms), the survival rate was significantly lower in the group whose QTc interval at 1 month after LTx decreased by >35ms (P=0.019).LTx in patients with end-stage lung disease may induce ECG changes. Patients whose QTc interval at 1 month after LTx decreased by >35ms have a significantly higher 1-year mortality rate. Hence, these ECG changes may have clinical and prognostic significance.